Lost and found family ebook A novel. - Ryan, Jennifer (2021)
If you love Jill Shalvis, Lori Wilde, and Susan Mallery, then you won't want to miss New York Times bestselling author Jennifer Ryan's riveting new novel about family, secrets, and a woman ready to embrace who she really is by facing down her past. As Sarah Anderson drives up to the house in Carmel, she knows she's on an impossible quest to make peace with the one person who truly hates her. For years, Sarah has hidden the truth about her late husband's lies from their children and their grandmother. When her mother-in-law, Margaret, threatens her with legal action to see the boys, Sarah strikes a bargain: she'll bring them for a six-week visit, hoping the boys, at least, will find connection and happiness with their extended family. It doesn't help that attorney and part-time rancher Luke Thompson lives right next door, and as an old friend of the family's he's agreed to investigate Sarah's past. Luke doesn't feel comfortable poking around in the very successful tech CEO's private life. What he finds is a truth very different from the one he's been led to believe. Far from being cold and unloving, Sarah is devoted to her boys and as at home on the ranch as she is in a boardroom. All Sarah ever wanted was a family, and all Luke wants now is her love. The time has come to reveal the terrible secrets that have been kept for so long. In losing the past, a new love—and family—can be found.